Taxonomic notes on Lepanthes disticha (Orchidaceae: Pleurothallidinae) and its allies in Mexico and Northern Central America - Catling, Paul M.; Salazar, Gerardo A. (Instituto de Ecología, A.C., 1994)
The terminal shape of the leaf was found to be correlated with other morphological features and with flower colour in the group of Lepanthes with black sheaths from Mexico and northern Central America. Plants with rounded-acute leaf tips, and the appendix inconspicuous and either with a solid portion less than 0.1 mm long or reduced to a tuft of hairs include Lepanthes nigriscapa R. E. Schult. & G. W. Dillon, L. quetzalensis Luer & Béhar and L. scopula Schltr.; L. inaequiloba Ames & C. Schweinf. has similar leaves but lacks entirely an appendix. Lepanthes nigriscapa is known only from the type material and is distinguished by a total absence of a solid appendix as well as by its divergent lateral sepals. Plants with acuminate leaves and prominent hairy appendix were first described by A. Richard and Galeotti as Pleurothallis disticha and later tranferred to Lepanthes by Garay and R. E. Schultes. Lepanthes oestlundiana R. E. Schult. & G. W. Dillon and L. pristidis Rchb. f. are best treated as synonyms  of L. disticha. Material reported as Lepanthes inaequiloba Ames & C. Schweinf. from Belize and as L. turialvae Rchb.f. from Guatemala is all referable to L. disticha. Another species with acuminate leaves and black sheaths, Lepanthes hondurensis Ames, apparently endemic to Honduras, is closely related to L. disticha, but differs in having the lobes of the petals subequal, broadly elliptic or rounded, and a glabrous appendix. Typification, synonymy and a key to the species are included.